(untitled) (Dhaka University Journal of Biological Sciences, 2023)
An investigation was carried out to study lichen flora of National Botanical Garden, Dhaka, during the tenure of May 2018 to April 2019. Seven genera of lichens namely Chrysothrix, Cladonia, Cryptothecia, Herpothallon, Parmelia, Pertusaria and Usnea were recorded from 15 blocks of the Garden. Lichens were abundantly grown and their number increased from June to October, whereas from November to April the number of lichens gradually decreased. The maximum frequency percentage (36.52) of the association found in Parmelia while minimum frequency percentage was recorded 2.48 in Usnea. Among three different heights, the highest number of lichens was recorded within 2 to 4 feet. Most exclusively, Parmelia was found in all the studied blocks, whereas other identified lichens were observed randomly. The present investigation will be helpful to enrich the knowledge on lichen biota of Bangladesh. Dhaka Univ. J. Biol. Sci. 31(2): 273-280, 2022 (July)